Opposing effects of in vitro differentiated macrophages sub-type on epithelial wound healing. - Julia A Gindele; Samuel Mang; Nicolas Pairet; Ingrid Christ; Florian Gantner; Jürgen Schymeinsky; David J Lamb (PLoS ONE, 2017)
Inappropriate repair responses to pulmonary epithelial injury have been linked to perturbation of epithelial barrier function and airway remodelling in a number of respiratory diseases, including chronic obstructive pulmonary disease and idiopathic pulmonary fibrosis. We developed an in vitro mechanical scratch injury model in air-liquid interface differentiated primary human small airway epithelial cells that recapitulates many of the characteristics observed during epithelial wound injury in both human tissue and small animal models. Wound closure was initially associated with de-differentiation of the differentiated apical cells and rapid migration into the wound site, followed by proliferation of apical cells behind the wound edge, together with increases in FAK expression, fibronectin and reduction in PAI-1 which collectively facilitate cell motility and extracellular matrix deposition. Macrophages are intimately involved in wound repair so we sought to investigate the role of macrophage sub-types on this process in a novel primary human co-culture model. M1 macrophages promoted FAK expression and both M1 and M2 macrophages promoted epithelial de-differentiation. Interestingly, M2a macrophages inhibited both proliferation and fibronectin expression, possibly via the retinoic acid pathway, whereas M2b and M2c macrophages prevented fibronectin deposition, possibly via MMP expression. Collectively these data highlight the complex nature of epithelial wound closure, the differential impact of macrophage sub-types on this process, and the heterogenic and non-delineated function of these macrophages.